Effect of induced alkalosis on performance during a field-simulated BMX cycling competition. Issue 3 (March 2019) - Peinado, Ana B.; Holgado, Darías; Luque-Casado, Antonio; Rojo-Tirado, Miguel A.; Sanabria, Daniel; González, Coral; Mateo-March, Manuel; Sánchez-Muñoz, Cristóbal; Calderón, Francisco J.; Zabala, Mikel
Abstract: Objectives: The aim of the present study was to test the effect of sodium bicarbonate (NaHCO3 − ) ingestion on performance during a simulated competition on a Bicycle Motocross (BMX) track. Design: Double-blind cross-over study. Methods: Twelve elite male BMX cyclists (age: 19.2 ± 3.4 years; height: 174.2 ± 5.3 cm; body mass: 72.4 ± 8.4 kg) ingested either NaHCO3- (0.3 g.kg −1 body weight) or placebo 90 min prior to exercise. The cyclists completed three races in a BMX Olympic track interspersed with 15 min of recovery. Blood samples were collected to assess the blood acid-base status. Performance, cardiorespiratory, heart rate variability (HRV) as well as subjective variables were assessed. Results: The main effect of condition (NaHCO3 − vs. placebo) was observed in pH, bicarbonate concentration and base excess (p < 0.05), with a significant blood alkalosis. No changes were found in time, peak velocity and time to peak velocity for condition (p > 0.05). The HRV analysis showed a significant effect of NaHCO3 − ingestion, expressed by the rMSSD30 (root mean square of the successive differences) (p < 0.001). There was no effect of condition on oxygen uptake, carbon dioxide production, or pulmonary ventilation (p > 0.05). Finally, there was no effect of condition for any subjective scale (p > 0.05). Conclusions: We present here the first field condition study to investigate the effect of bicarbonate ingestion over performance in BMX discipline. The results showed that NaHCO3 − -induced alkalosis did not improve performance in a simulated BMX competition in elite BMX cyclists, although future studies should consider the effects of NaHCO3- on autonomic function as a component of recovery.